Umbellaceae fam. nov. (Hymenochaetales, Basidiomycota) for Umbellus sinensis gen. et sp. nov. and Three New Combinations - Xue-Wei Wang; Li-Wei Zhou (Journal of Fungi, 2023)
Hymenochaetales, belonging to Agaricomycetes, Basidiomycota, comprises most polypores and corticioid fungi and, also, a few agarics. The latest taxonomic framework accepts 14 families in this order. When further exploring species diversity of Hymenochaetales, two corticioid specimens collected from China producing cystidia with large umbrella-shaped crystalline heads attracted our attention. This kind of cystidia was reported only in three unsequenced species, viz. Tubulicrinis corneri, T. hamatus and T. umbraculus, which were accepted in Tubulicrinaceae, Hymenochaetales. The current multilocus-based phylogeny supports that the two Chinese specimens formed an independent lineage from Tubulicrinaceae as well as the additional 13 families and all sampled genera in Hymenochaetales. Therefore, a monotypic family, Umbellaceae, is newly described with the new genus Umbellus as the type genus to represent this lineage. The two Chinese specimens are newly described as U. sinensis, which differs from T. corneri, T. hamatus, and T. umbraculus in a combination of a smooth to grandinioid hymenophoral surface, not flattened, broadly ellipsoid basidiospores with a tiny apiculus, and growth on angiosperm wood. Due to the presence of the unique cystidia, the three species of Tubulicrinis, even though they lack available molecular sequences, are transferred to Umbellus as U. corneri, U. hamatus, and U. umbraculus. Hereafter, all known species with large umbrella-shaped crystalline-headed cystidia are in a single genus. In summary, the current study provides a supplement to the latest taxonomic framework of Hymenochaetales and will help to further explore species diversity and the evolution of this fungal order.